Prevalence of bacteriuria and bacterial resistance in adolescents from the center of the state of Tlaxcala, Mexico - Daniela Z. Méndez-Polonieski; Pablo Méndez-Hernández; Olivier Barbier; Manolo Ortega-Romero; Juan C. Rubio-Gutiérrez; Elodia Rojas-Lima; Juana Narvaez-Morales; Margarita Martínez-Gómez; Estela Cuevas-Romero; Rosalba Cerón-Meza; Mara Medeiros (Permanyer, 2024)
Urinary tract infections and bacteriuria are common in the pediatric population, and antibiotic resistance is increasing significantly. Recurrent urinary infections, symptomatic or asymptomatic, are a risk factor for developing chronic kidney disease in adolescents and young adults. This study aimed to assess the prevalence of bacteriuria diagnosed by culture to identify the main causal agents and sensitivity to antibiotics in adolescents from the central region of the state of Tlaxcala. A cross-sectional study was carried out among 905 adolescents from 11 to 18 years old who lived in the central region of the state of Tlaxcala, Mexico. Bacteriuria was evaluated by positive nitrites and leukocyte esterase, and urine culture with antibiogram. Multivariate logistic regression models were executed to evaluate the risk of presenting bacteriuria, with a confidence level of 95%. A total of 31 participants had a positive urine culture, with a bacteriuria prevalence of 3.4%, of which 29 cases were asymptomatic. The most frequent agent was Escherichia coli) in both sexes (28.6% in men and 29.7% in women) and regarding bacterial resistance: E. coli presented greater resistance to ampicillin, trimethoprim/sulfametoxazol and ceftriaxone. The risk factors associated with bacteriuria were female sex, sexual activity, use of contraceptives, and greater consumption of sweetened beverages. Bacteriuria is common in this adolescent population, so its early identification is necessary to treat it, and to prevent its complications.